A3.4 CD3+CD4–CD8– Double Negative Th17 Cells: New Insights in the Pathogenesis of Primary Sjögren's Syndrome. (25th February 2013) - Alunno, Alessia; Caterbi, Sara; Bistoni, Onelia; Bartoloni, Elena; Santoboni, Gianluca; Mirabelli, Giulia; Cannarile, Francesca; Valentini, Valentina; Terenzi, Riccardo; Gerli, Roberto
Abstract : Background and Objectives: IL-17 axis is widely recognised to be involved in the pathogenesis of autoimmune disorders. Besides conventional CD4 + Th17 cells, a small IL-17 producing T-cell population, that lacks of both CD4 and CD8 molecules, defined as double negative (DN) was recently found to be expanded in the peripheral blood (PB) and to accumulate in the kidney in patients with lupus nephritis. Since IL-17 production is enhanced in minor salivary gland (MSG) infiltrates of patients with primary Sjögren's syndrome (pSS), we sought to investigate whether DN T cells may be involved in pSS pathogenesis. Materials and Methods: Thirty patients with pSS and 16 normal controls (NC) were studied. PBMCs were separated by density gradient and phenotypic characterisation was performed by flow cytometry on both freshly isolated cells and after culture (24, 48, 72 and 96 hours). Total PBMCs were cultured in anti-CD3 coated plates in presence or absence of dexamethasone (Dex) at different concentrations. In selected experiments, real time PCR at the same time-points was performed. The study of pSS-MSGs was performed by immunofluorescence. Results: Total circulating DN T cells were increased in pSS compared to NC. NC and pSS freshly isolated DN T cells expressed RORγ t, activation markers (CD25, CD69, HLA-DR) and produced consistent amounts of IL-17. Despite IL-6/TGFβ ratio became abnormal in pSS patients after 72 hour-culture, Dex was able to down-regulate IL-17 in vitro production in NC and pSS CD4 + Th17 cells and in NC DN T cells from this time-point on. Surprisingly, IL-17 production by pSS-DN T cells was not affected at all by Dex at any time-point. Dex could also reduce the expression of activation markers on CD4 + cells, but not in pSS and NC-DN T cells. Among DN T cells, those expressing αβTCR were expanded in patients with active pSS compared to those with inactive pSS. DN T cells were present in pSS-MSG infiltrate. Conclusions: To our knowledge, this is the first study identifying and characterising DN T cells in pSS. It shows that DN T cells are expanded in the PB of pSS, display an in vivo activated Th17 phenotype, infiltrate MSG and are resistant to corticosteroids. Taken together, these data suggest a key role of this T-cell subset in the perpetuation of chronic sialoadenitis and eventually in SS prognosis and provide the clue to target DN T cells for therapeutic purposes in pSS.